Initial knowledge of geoscience camps' participants analysed by the association technique - Pražáková, Martina; Pavlasová, Lenka (Scientia in educatione, 2019)
Knowledge testing is a key part of formal education. However, it is rarely used in nonformal education. This research describes an analysis based on a two-dimensional approach to pupils’ cognitive knowledge. It was performed by a word association test which helps the examiners ascertain the pupils’ real understanding (n = 143) of geoscience. Its outcomes define the level of initial theoretical and practical knowledge of geoscience camp participants’ in the following four dimensions of knowledge: factual, conceptual, procedural and metacognitive. It proves that older pupils (older than 12 years) and girls show statistically significantly higher level of theoretical conceptual knowledge. Therefore, our recommendation for teaching the geoscience topics in non-formal education is to emphasize the practical abilities of pupils, which are specific to this area of natural science and whose deficiency we can perceive. For pupils interested in geoscience, non-formal education might become a convenient addition to the formal one.